TACKLING THE PAINS OF CORONAVIRUS LOCKDOWN THROUGH PALLIATIVES IN NIGERIA: ADDRESSING THE GAPS AND CRITICAL STRATEGIC ISSUES - N. ONAH, Ph.D, FRANCISCA; O. UGWUIBE, Ph.D, CHRISTOPHER; O. ONAH Ph.D, FAB. (International Journal of Psychosocial Rehabilitation, 2021)
On March 11, 2020 the World Health Organization (WHO) upgraded the status of thenovel coronavirus, also known as COVID-19 outbreak, from epidemic to pandemic. Eversince then, the world has been reeling from the catastrophic spread of the virus.Consequently, Nigeria rolled out a couple of measures to reduce the spread of the virusin the country in keeping with WHO guides. In addition, the Federal Government andmost States in the Federation declared lockdown in the state and closure of states andnational borders. The study investigated the effectiveness and interrogated the templateused in distributing the palliatives to the poor. The results showed that the templates usedin the distribution of the palliatives were highly ineffective and that inadequate data baseand politics negatively impacted on the implementation of the palliatives meant for thepoor. The study recommended among others that for strategic reasons ,sufficient anddisaggregated data should be generated, updated, and stored for future use in Nigeriafor the purpose of bringing the warmth of governance to all who are in need